Signs Found in San Andreas Movie - Putu Intan Mayang Sari, Ni; Nyoman Sujaya, I; Umiyati, Mirsa (KnE Social Sciences, 2022)
Humans, as social beings, must always communicate with others in their daily lives. Language is certainly used when communicating with others. The goal of this study was to identify, classify, and analyze the different types of signs and their functions in the San Andreas movie. This study employs a qualitative approach. The study’s findings revealed that signs can be found in movies. The movie ”San Andreas” served as a data source, demonstrating how different people use signs. Icon, Index, and Symbol are just some of the signs used here. Each sign has different functions as well. Ideational Metafunction, Interpersonal Metafunction, and Textual Metafunction are all parts of the sign’s function. Ideational Metafunction is one of the most prominent functions of the sign in the film ”San Andreas,” and it is most prominently displayed by the sign Icon. Icon, Index, and Symbol all contain Ideational Metafunction. In Index and Symbol, you’ll find Interpersonal Metafunction. Symbol and Index contain textual metafunction in this film. Keywords: sign, semiotics, San Andreas movie